2016
DOI: 10.1590/1519-6984.19014
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Tripartiella (Ciliophora: Trichodinidae) from Aequidens tetramerus (Perciformes: Cichlidae) in north Brazil

Abstract: A new species of Tripartiella is described from the gills of the wild saddle cichlid Aequidens tetramerus in north Brazil. Wet smears of skin and gills of examined fish were air-dried at room temperature and impregnated with Klein's dry silver method for examination of the adhesive disc's structures and denticles. Total prevalence of parasitism was 65%. This ciliate is characterized as a small-sized trichodinid, body diameter 37.03 ± 4.9 μm, adhesive disc 30.50 ± 2.71 μm, denticulate ring 13.28 ± 0.8 μm and 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…In this region, A. tetramerus was also found to be parasitized by Tripartiella tetramerii (Fig. 2), which was the first trichodinid described in the Amazon region (Martins et al 2016). It was observed that A. tetramerus acquired only this species of trichodinid, among the diversity of parasites found in its cohabitant O. niloticus, possibly because of difficulty in accessing a community of ectoparasites that already existed in native species.…”
Section: Trichodinids In Farmed Fish In Brazilmentioning
confidence: 88%
See 1 more Smart Citation
“…In this region, A. tetramerus was also found to be parasitized by Tripartiella tetramerii (Fig. 2), which was the first trichodinid described in the Amazon region (Martins et al 2016). It was observed that A. tetramerus acquired only this species of trichodinid, among the diversity of parasites found in its cohabitant O. niloticus, possibly because of difficulty in accessing a community of ectoparasites that already existed in native species.…”
Section: Trichodinids In Farmed Fish In Brazilmentioning
confidence: 88%
“…Organisms of the family Trichodinidae are commonly found in aquatic environments as symbionts. However, they can behave as commensals or parasites of a variety of aquatic vertebrates and invertebrates, such as ciliates, coelenterates planctophagous crustaceans, mollusks, echinoderms, amphibians and fish (Van As and Basson 1987;Basson and Van As 1989;Sabry and Magalhães 2005;Pinto et al 2006;Dias et al 2009;Silva-Briano et al 2011;Martins et al 2016). Trichodinid species are therefore of great importance for fish farming, given that they parasitize farmed fish.…”
Section: Introductionmentioning
confidence: 99%
“…Los miembros de la familia Trichodinidae Claus, 1951 se encuentran fundamentalmente en ambientes acuáticos como simbiontes. Además, se encuentran como comensales o parásitos de una gran variedad de invertebrados y vertebrados acuáticos, como crustáceos, moluscos, equinodermos, anfibios y peces (Basson y Van As, 1989;Sabry y Magalhães, 2005;Pinto et al, 2006;Dias et al, 2009;Silva-Briano et al, 2011;Martins et al, 2016).…”
Section: Discussionunclassified